Serine proteases in neutrophil extracellular traps exhibit anti-Respiratory Syncytial Virus activity - Lopes, Bruno Rafael Pereira [UNESP]; da Silva, Gabriel Soares [UNESP]; de Lima Menezes, Gabriela; de Oliveira, Juliana [UNESP]; Watanabe, Aripuanã Sakurada Aranha; Porto, Bárbara Nery; da Silva, Roosevelt Alves; Toledo, Karina Alves [UNESP] (Elsevier, 2022)
Human respiratory syncytial virus (hRSV) is an infectious agent in infants and young children which there are no vaccines or drugs for treatment. Neutrophils are recruited for airway, where they are stimulated by hRSV to release large amounts of neutrophil extracellular traps (NETs). NETs are compound by DNA and proteins, including microbicidal enzymes. They constitute a large part of the mucus accumulated in the lung of patients, compromising their breathing capacity. In contrast, NETs can capture/inactivate hRSV, but the molecules responsible for this effect are unknown. Objectives: We selected microbicidal NET enzymes (elastase, myeloperoxidase, cathepsin-G, and proteinase-3) to assess their anti-hRSV role. Methods and Results: Through in vitro assays using HEp-2 cells, we observed that elastase, proteinase-3, and cathepsin-G, but not myeloperoxidase, showed virucidal effects even at non-cytotoxic concentrations. Elastase and proteinase-3, but not cathepsin-G, cleaved viral F-protein, which is responsible for viral adhesion and fusion with the target cells. Molecular docking analysis indicated the interaction of these macromolecules in the antigenic regions of F-protein through the active regions of the enzymes. Conclusions: Serine proteases from NETs interact and inactive hRSV. These results contribute to the understanding the role of NETs in hRSV infection and to designing treatment strategies for the inflammatory process during respiratory infections.
Keywords: Neutrophils; Proteases; Respiratory syncytial virus; Virucidal